Etika Komunikasi Digital Perspektif Habermas, Foucault, dan Scheler dalam Konteks Indonesia - Subekti, Slamet (Respons: Jurnal Etika Sosial, 2024)
The digital revolution presents a dual impact on Indonesia's public sphere: unlocking democratic potential while simultaneously giving rise to complex pathologies such as hoaxes, polarization, and hate speech. This article argues that a partial ethical approach is inadequate to address these dynamics. Utilizing theoretical triangulation, this analysis integrates the perspectives of Jürgen Habermas, Michel Foucault, and Max Scheler to offer a holistic framework. Habermas provides the normative-procedural foundation concerning the ideal public sphere and communicative distortions. Foucault deconstructs power/knowledge relations and disciplinary mechanisms within the digital architecture. Meanwhile, Scheler complements this with an axiological foundation through material ethics of value and a critique of ressentiment. Contextual Indonesian case studies demonstrate that these three perspectives complement each other dialectically. It is concluded that an effective digital communication ethics requires a three-layered integration: (1) strengthening deliberative-rational procedures (Habermas); (2) maintaining critical vigilance towards power (Foucault); and (3) building character based on values and the education of feeling (Scheler). This synthesis is expected to guide Indonesia's digital ecosystem towards becoming a space that is not only intelligent but also just and humane.